Retrospective observational cohort study of premature neonates screened for ROP with 7 years of follow-up assessing the visual outcomes and adequacy of preschool visual screening - Emma McAllister; Ruth Hamilton; Eoghan Millar; Alasdair Innes Simpson; Jacqueline Wright (BMJ Open Ophthalmology)
Background Very premature infants screened for retinopathy of prematurity (ROP) that do not develop ROP still experience serious visual developmental challenges, and while it is recommended that all children in the UK are offered preschool visual screening, we aimed to explore whether this vulnerable group requires dedicated follow-up.Methods We performed a real-world retrospective observational cohort study of children previously screened for ROP in NHS Greater Glasgow and Clyde (Scotland) between 2013 and 2015. We excluded those with any severity of ROP identified during screening. Electronic patient records were searched for preschool orthoptic visual screening (See4School) results and results of referral to the hospital eye service (HES).Results 222 children met the inclusion criteria. Their median birth weight was 1200 g and median gestational age was 31 weeks. A total of 111 (50%) of these children had been referred to HES nationally. 103 were referred within the health board where ROP screening took place; of these, 47% (48/103) were referred from the See4School programme, 31% (31/103) from paediatric clinics, 13% (13/103) from primary care and 11% (11/103) from community optometrists. 42 of these 103 referrals (41%) to HES had occurred before the age (3½ years) when children became eligible for See4School screening. At hospital review, 55% (55/99) patients had a glasses prescription issued for refractive error, 22% were estimated to have amblyopia and 30% had a diagnosis of strabismus.Conclusion In this non-controlled study we found premature infants that do not develop ROP still face considerable visual morbidity and dedicated follow-up may be warranted.